Biodiversity conservation and threat reduction in Kibale and Queen Elizabeth conservation areas, Uganda - Joseph Katswera; Norah M. Mutekanga; Charles K.Twesigye (East African Journal of Biophysical and Computational Sciences)
This paper examines threats affecting the wildlife conservation areas, threat reduction and adaptive management strategies that enhance biodiversity conservation. The research for this paper was conducted through a survey, and data was collected from August 2018 to April 2019 in Kibale and Queen Elizabeth Conservation Areas using literature review, threat reduction assessment technique, Key Informant Interviews and Focused Group Discussions and semi-structured questionnaires. The data was analysed using Geographical Information System software ESRI ArcGIS version 10.31, threat reduction assessment tool, Pearson Chi square test, Spearman’s rho correlation coefficient, Paired Samples t Test, and one-way Analysis of Variables; and presented in tables and figures. The study established that staff education level and experience in conservation work influences biodiversity conservation. The conservation areas are threatened by habitat transition/changes, wild fires, human-wildlife conflicts, armed poaching and illegal wildlife trade/trafficking in game meat and game products, increasing human population pressure, and boundary encroachment. Despite these threats, there was a general increase in large mammal population over the past decades, which collaborates well with the threat reduction assessment indices. Both conservation areas had an ecological integrity rating average score of “yellow” indicating significant “concern” and therefore “dissatisfactory”. The two conservation areas are majorly threatened by anthropogenic threats, natural threats, and administrative constraints. The wildlife agency should integrate ecosystem health into the conservation agenda. The agency should also strengthen adaptive management, law enforcement, and collaboration with local communities and other stakeholders to reduce on the threats. Finally, further research should focus on ecosystem health, and also the impact of tourism infrastructural development on biodiversity conservation.